2021
DOI: 10.1371/journal.pone.0247686
|View full text |Cite
|
Sign up to set email alerts
|

Time series analysis of the demand for COVID-19 related chest imaging during the first wave of the SARS-CoV-2 pandemic: An explorative study

Abstract: Objectives The aim of this study was to investigate possible patterns of demand for chest imaging during the first wave of the SARS-CoV-2 pandemic and derive a decision aid for the allocation of resources in future pandemic challenges. Materials and methods Time data of requests for patients with suspected or confirmed coronavirus disease 2019 (COVID-19) lung disease were analyzed between February 27th and May 27th 2020. A multinomial logistic regression model was used to evaluate differences in the number o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…This was to help manage increases in patient presentations during viral surges and manage workflow. This staffing adjustment is supported by Koehler et al, who investigated the demand for chest imaging during the pandemic’s first wave 37 . The greatest demand for chest imaging was between 2 and 10 pm for emergency patients and 6 am to 2 pm for inpatient requests 37 .…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…This was to help manage increases in patient presentations during viral surges and manage workflow. This staffing adjustment is supported by Koehler et al, who investigated the demand for chest imaging during the pandemic’s first wave 37 . The greatest demand for chest imaging was between 2 and 10 pm for emergency patients and 6 am to 2 pm for inpatient requests 37 .…”
Section: Discussionmentioning
confidence: 97%
“… 37 The greatest demand for chest imaging was between 2 and 10 pm for emergency patients and 6 am to 2 pm for inpatient requests. 37 The radiographers rostered to mobiles did not separate into teams without crossover; however, others considered this work practice. 5 While additional staff may improve workflow during the peak period, health services are well placed to manage any changes in demand.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also observed that fixed X-ray imaging decreased when adult mobile imaging increased in the emergency setting. This was likely to reduce transmission risk and manage potential increased demand[ 8 , 32 ]. The greatest impact on adult mobile imaging usage was observed during the pandemic’s second wave, when the risk of cold and influenza was heightened (July-September 2020)[ 33 ].…”
Section: Discussionmentioning
confidence: 99%